If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + -3) + -3(5x + 6) = -4(-3x + 5) + 5(-4x + 5) Reorder the terms: 7(-3 + 2x) + -3(5x + 6) = -4(-3x + 5) + 5(-4x + 5) (-3 * 7 + 2x * 7) + -3(5x + 6) = -4(-3x + 5) + 5(-4x + 5) (-21 + 14x) + -3(5x + 6) = -4(-3x + 5) + 5(-4x + 5) Reorder the terms: -21 + 14x + -3(6 + 5x) = -4(-3x + 5) + 5(-4x + 5) -21 + 14x + (6 * -3 + 5x * -3) = -4(-3x + 5) + 5(-4x + 5) -21 + 14x + (-18 + -15x) = -4(-3x + 5) + 5(-4x + 5) Reorder the terms: -21 + -18 + 14x + -15x = -4(-3x + 5) + 5(-4x + 5) Combine like terms: -21 + -18 = -39 -39 + 14x + -15x = -4(-3x + 5) + 5(-4x + 5) Combine like terms: 14x + -15x = -1x -39 + -1x = -4(-3x + 5) + 5(-4x + 5) Reorder the terms: -39 + -1x = -4(5 + -3x) + 5(-4x + 5) -39 + -1x = (5 * -4 + -3x * -4) + 5(-4x + 5) -39 + -1x = (-20 + 12x) + 5(-4x + 5) Reorder the terms: -39 + -1x = -20 + 12x + 5(5 + -4x) -39 + -1x = -20 + 12x + (5 * 5 + -4x * 5) -39 + -1x = -20 + 12x + (25 + -20x) Reorder the terms: -39 + -1x = -20 + 25 + 12x + -20x Combine like terms: -20 + 25 = 5 -39 + -1x = 5 + 12x + -20x Combine like terms: 12x + -20x = -8x -39 + -1x = 5 + -8x Solving -39 + -1x = 5 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -39 + -1x + 8x = 5 + -8x + 8x Combine like terms: -1x + 8x = 7x -39 + 7x = 5 + -8x + 8x Combine like terms: -8x + 8x = 0 -39 + 7x = 5 + 0 -39 + 7x = 5 Add '39' to each side of the equation. -39 + 39 + 7x = 5 + 39 Combine like terms: -39 + 39 = 0 0 + 7x = 5 + 39 7x = 5 + 39 Combine like terms: 5 + 39 = 44 7x = 44 Divide each side by '7'. x = 6.285714286 Simplifying x = 6.285714286
| 12-7b=18-9b | | 4x+8y=-44 | | ax+5=bx-cforx | | 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 | | 10-3c=10+9c | | 1x+7=2x+3 | | 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 | | 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 | | 6p+5=17 | | 2(x^2-7x+21)=0 | | 502.4=3.14(4)h | | Y-x=-9 | | 30+x=167 | | .5(2n-3)-.1=.4(6+2n) |